An ethnobotanical study of medicinal plants in Palamalai region of Eastern Ghats, India. (22nd August 2015) - Silambarasan, Rajendran; Ayyanar, Muniappan
Abstract: Ethnopharmacological relevance: During the last few decades there has been an increasing interest in the study of medicinal plants with their traditional use and related pharmacological research all over the World. This paper enumerated folk medicinal plants used by Malayali tribal people in an unexplored and biodiversity rich region of Eastern Ghats in southern India. Aim of study: The aim of this study is to collect and identify the plants used in medicinal therapy by the local people and professional traditional healers with quantitative analysis. Materials and methods: An ethnobotanical survey was carried out during January to December 2014 among the Malayali tribal people in four villages of Palamalai region in Eastern Ghats, India. The information was obtained through open and semi-structured face-to-face interviews with the local knowledgeable people and professional traditional healers. The statistical analysis, use value, family use value, informants' consensus factor, fidelity level, frequency of citation, relative frequency citation and informants' agreements ratio were calculated for the quantitative study of ethnomedicinal data. Results: A total of 118 plant species belonging to 95 genera and 55 families dominated by the families like Leguminosae, Asteraceae and Lamiaceae were enumerated with detailed information on parts used, method of preparation, mode of administration and ailments treated. Leaves were mostly used plant part and predominantly used herbal preparations were decoction and paste. Moringa oleifera Lam. was reported by all the interviewed informants and gives the highest UV of 3.9 with 78 use reports due to its diverse medicinal uses. Conclusion: The present study demonstrated the need for importance of documenting the traditional knowledge of forest dwelling people. As a result of the study, Abutilon indicum (L.) Sweet., Andrographis echioides (L.f.) Nees., Bacopa monnieri (L.) Wettst., Canarium strictum Roxb., Centella asiatica (L.) Urban., Senna auriculata (L.) Roxb. and Tribulus terrestris (L.) were recommended for further ethnopharmacological studies since these plants were recorded with high UV, IAR, RFC and FL values. Graphical abstract: